Identifikasi dan Toleransi Kemasaman Mesofauna Indigenous Tanaman Lada untuk Pertumbuhan Bibit Lada (Piper nigrum L.): Identifikasi dan Toleransi Kemasaman Mesofauna Indigenous Tanaman Lada untuk Pertumbuhan Bibit Lada (Piper nigrum L.) - Ratna Santi; Gusmaini Gusmaini; Mamik Sarwendah (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2020)
Low soil fertility in Bangka becomes the main problem in permanent pattern of pepper cultivation. Utilization of micro and mesofauna plays a role in the decomposition of organic matter, improving soil structure, recycling of nutrients and reducing nutrient loss. This study aims to identify the potential of mesophuna isolation under the stand of pepper in stimulating the growth pepper seedlings. The initial stage of the activity is the identification and analysis of the abundance of mesofauna soil samples taken from South Bangka production centers of pepper plants. The potential tolerance of mesofauna acidity by growing pot system nursery pepper at different media acidity levels. The results showed that mesofauna obtained from Acari and Collembola species from Neanuridae family, Hypogastruridae, Entomobrydae, Sminthuridae, Cypoderidae, Mesotigmata. Based on tolerance to mesophyroid pH identified in this study are indifferent groups living on acid and alkaline pH conditions. Mesofauna can improve soil fertility as indicated by an increasing C-organic content, macro nutrients P, K, soil pH and soil aeration. Increasing macro nutrients and improving soil porosity of the planting media will stimulate root development and growth of nursery pepper.